Oral language in children with benign childhood epilepsy with centrotemporal spikes - Teixeira, Joana Marta (2020)
Purpose: Benign childhood epilepsy with centrotemporal spikes is one of the most common childhood disorders. Despite the benignity usually attributed to this epileptic syndrome, several studies have demonstrated that these children have cognitive disabilities. Among these disturbances, language disorders have been the less studied in depth. We aimed to obtain accurate information about the language skills of children with this epileptic syndrome and to explore the correlation between demographic and clinical factors associated with epilepsy and the language skills. Methods: We assessed 30 children with this epileptic syndrome, followed in three hospitals in Lisbon, and 60 controls, aged between 6 and 12 years, attending the same schools and matched by age, gender, and parents' socioprofessional level. All the included children did not present cognitive impairment (reasoning ability, verbal memory), sensory, or motor limitations. The evaluation tests covered all language areas. Results: Overall, children with this epileptic syndrome had lower skills in the majority of the language areas, when compared with their peers. These children showed greater difficulties in semantics and syntax domains. The atypical evolution of the seizures and a longer duration of epilepsy were the clinical variables that most influence the language skills of our samples. Conclusion: The early assessment of these capacities and the possible need for therapeutic intervention should be emphasized, in order to minimize the impact on their academic performance and quality of life